On the Construction of Religious Texts: The Case of Writing a Catechism - Pleizier, Theo (NTT, 2020)
Religious texts represent a specific rhetorical genre. What does it mean to construct these texts? In order to answer this question we reflect upon our experience of co-authoring a religious text, the Ordinary Catechism (Gewone Catechismus), published in 2019. The findings include insights in collaborative spirituality, a dynamic interaction with tradition, and various levels of abstraction in theologizing. Further, we analyze these findings by using genre theory. It is concluded that religious texts are responses to a rhetorical situation; they are part of genre repertoires that religious communities use to express and to experience the Christian faith.